STUDY GRADE HAZARD OF SLIDE INTHE KOTO PARIK GADANG DIATEHSUBDISTRICT SOUTHSOLOKREGENCY - Ismayani, Nina; Hermon, Dedi; Juita, Erna (Pendidikan Geografi, 2013)
This experiment have a purpose to describe about characteristic a land in the Koto Parik Gadang Diateh Subdistrict South Solok Regency, the grade of slide hazard in the Koto Parik Gadang Diateh Subdistrict South Solok Regency and spatial share the grade of slide in the Koto Parik Gadang Diateh Subdistrict South Solok Regency.The genre of the experiment is describe with use a metod survey, data source is primer data result direct in the field and labororatorium, whereas sekunder data is a reference source and analytical result in the library. Experiment technic is use a stratified random technik. Data analytical technic is characteristic analytical land with describtive and ditabulation from criteria data act to physical phenomena to determining hazard of the slide, analytical for determine grade of denger slide and share spatial grade of hazard slide with the analytical and process that. The product of experiment explain about: characteristic the land in the experiment zone have 7 land squad grade of hazard slide is: (1) grade of hazard slide is low where in the land squade VI.Qpt.I.Pem.Gleih. (2) grade of hazard slide is medium exist in the land squade V3.Mip.III.Pem.Gleih and V3.Qal.III.Pem.Gleih. (3) grade of hazard slide is hing exist in the land squade V4.Mpip.IV.Pem.Gleih, V4.Qal.IV.Pem.Gleih, and V4.Qvbe.IV.Pem.Gleih and share spatial about study grade of hazard slide have a slore flat (0-13%), slope-asistant (14-25%) and sheer (26-40%) is a part from Nagari Pakan Rabaa North border zone between Solok Regency with South Solok Regency and Nagari Pakan Rabaa Tengah zone north Pakan Rabaa Utara zone south and Nagari Pakan Rabaa.